Saint Lucia. Annual report 2008 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
Presents the results of IICA in Saint Lucia in 2009 in relation to the state of agriculture and rural life, the implementation of the national technical cooperation agenda, inter-agency cooperation, horizontal technical cooperation, new opportunities for technical cooperation and organized activities